The Variaton Of Language Functions On The Social Media Instagram Account @dolanboyolali - Muslikah (Universitas Negeri Surabaya, 2023)
Language becomes an important element in communicating, with the presence of human language can convey information, messages, and purposes. However, there are several factors that make a language have a variety of variations, such as casual variations, formal variations, dialects, and chronoleces. This is due to the classification of language based on the wearer and its function. The language can be divided into two, namely written language and spoken language. Writing language for example description of uploads on social media. The study aims to identify the variations of language contained on Instagram’s social media account @dolanboyolali. This research uses qualitative descriptive methods, with noting techniques. The data source of this study is a description (caption) in Instagram post @dolanboyolali taken in December 2022 and January 2023. The results of the study are different business languages, raw languages, casual languages, and varieties of familiar languages. Keywords: language variation, social media, Instagram